2019
DOI: 10.1007/s11187-019-00179-0
|View full text |Cite
|
Sign up to set email alerts
|

Retirement of the self-employed in the Netherlands

Abstract: We investigate retirement decisions of the self-employed in the Netherlands using administrative data. We focus on the time period around which individuals reach the statutory retirement age (SRA, 65 years in most cases). After the statutory retirement age, each Dutch resident receives the Old Age State Pension annuity (AOW), providing an income at the subsistence level. Both the timing and the magnitude of this state pension are well known in advance. According to a standard leisure/consumption trade-off life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Prior evidence has shown that households are very responsive to the (change in) institutional retirement ages which causes discontinuous retirement probabilities right before and after reaching the retirement age (see, among others, Duggan et al (2007)). Such evidence of responsiveness to the statutory retirement age is also found for the Netherlands in recent papers by Atav et al (2021) and Nagore Garcia et al (2021). For a more extensive discussion on the discontinuity, we refer to Been and Goudswaard (2021).…”
Section: D2 Discontinuities In the Dutch Pension Systemsupporting
confidence: 76%
“…Prior evidence has shown that households are very responsive to the (change in) institutional retirement ages which causes discontinuous retirement probabilities right before and after reaching the retirement age (see, among others, Duggan et al (2007)). Such evidence of responsiveness to the statutory retirement age is also found for the Netherlands in recent papers by Atav et al (2021) and Nagore Garcia et al (2021). For a more extensive discussion on the discontinuity, we refer to Been and Goudswaard (2021).…”
Section: D2 Discontinuities In the Dutch Pension Systemsupporting
confidence: 76%
“…This restriction allows us to remove seasonal laborers and other workers that are likely to exit the firm before the SRA. 19 We also exclude workers that are directors or shareholders of their firms, since their retirement incentives are more complex and they are less responsive to the SRA (Atav et al, forthcoming;Nagore García et al, 2021).…”
mentioning
confidence: 99%